Challenges and Improvements in Safety Assurance Implementation at Aviation Training Organizations - Nugraha, Wildan; Komalasari, Yeti; Hariri, Achmad; Pesilette, Mohammad Sukri; Abdullah, Anton; Masito, Fitri; Sutiyo, Sutiyo; Andayani, Thursina (Yayasan Sembilan Pemuda Indonesia, 2025)
Aviation safety is the primary foundation for the sustainability and credibility of the global aviation industry. To strengthen the safety system, the International Civil Aviation Organization (ICAO) requires all aviation organizations, including Approved Training Organizations (ATOs), to implement a Safety Management System (SMS) consisting of four main pillars, namely Safety Policy, Safety Risk Management, Safety Assurance, and Safety Promotion. The Safety Assurance element plays a strategic role as an internal monitoring mechanism to ensure that the safety strategies, policies, and processes implemented are running effectively and sustainably. This study evaluates the implementation of SMS at Palembang Aviation Polytechnic, an ATO in Indonesia. Using a mixed-methods approach, data were collected from 45 personnel via Likert-scale questionnaires, interviews, and document analysis. Results indicate strong performance in internal audits (mean = 4.04) and safety monitoring (mean = 3.77), but weaknesses in hazard reporting (mean = 3.31) and change management (mean = 3.33). Qualitative findings reveal a fear-based reporting culture and reactive change processes. Triangulation highlights gaps between perception and practice, emphasizing the need for a ‘Just Culture’ framework and risk-based change management. The study contributes a model for enhancing SMS in aviation education, addressing a critical gap in non-elite ATO contexts.